Race and sex differences in adverse childhood experiences among Asian/Pacific Islander college students. Issue 4 (8th June 2021) - Sieben, Andrew; Lust, Katherine; Crose, Ainslee; Renner, Lynette M.; Nguyen, Ruby H. N.
Abstract: Objective: Adverse childhood experiences (ACEs) may be detrimental to health, yet are understudied in Asians/Pacific Islanders (API). We described the prevalence of individual ACEs among API college students compared to White college students. Participants: College students ( n  = 8, 472) from 17 Minnesota postsecondary institutions completed the College Student Health Survey in spring 2015. Methods: Students self-reported on 11 ACEs. We assessed differences in prevalence of individual ACEs between APIs and Whites. Results: APIs were more likely to report having been physically abused (adj. OR = 2.04), verbally abused (adj. OR = 1.25), and raped (adj. OR = 1.75) relative to Whites. Stratification by sex showed API males were more likely to have been sexually abused relative to White males, with additional ACEs differing significantly by sex and race. Conclusions: Individual ACE prevalence differed between APIs and Whites and is often sex-specific. Additional research is needed to estimate ACE prevalence in other racial/ethnic groups and their health impacts.